(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2021)
The phytoplankton dynamics in the Debed River, Armenia, was investigated. Water samples for phytoplankton quantitative and qualitative analyses were collected from 4 sites along the river once per season in April, July and September 2017. The results of the study have revealed the characteristics of the spatiotemporal distribution of phytoplankton community in the Debed River.